Co-Citation Network Investigation Using Management of Technology (MOT) - Vimal Kumar Stephen. K; V. Mathivanan (Indonesian Journal of Electrical Engineering and Computer Science, 2017)
This paper reports a co-citation network investigation (bibliometric investigation) of 10 journals in the management of technology (MOT) field. And also presenting different bibliometric thoughts, organize investigation devices recognize and investigate the ideas secured by the field and their between connections. Particular outcomes from various levels of investigation demonstrate the diverse measurements of technology administration: Co-word terms recognize subjects, Journal co-reference arrange: connecting to different controls, Co-citation network indicate groupings of topics. The examination demonstrates that MOT has a connecting part in coordinating thoughts from a few particular orders. This recommends administration and technique are vital to MOT which basically identifies with the firm as opposed to arrangement. Additionally we have a double concentrate on abilities, however can see inconspicuous contrasts by the way we see these thoughts, either through an inwards looking focal point to perceive how associations capacity, or all the more outward to comprehend setting and change in landscapes.